Executive alumni networks: Catalysts or constraints for innovation in China’s listed firms? - Guo, Jinzhong; Liu, Jianan; Li, Moxin; Liu, Xiaoling; Liu, Chengyong (Journal of data and information science (Warsaw, Poland), 2025)
NOABSTRACTCurrently, different research conclusions exist about the relationship between relational capital and corporate innovation. The research aims to (1) reveal the actual relationship between executive alumni relations and firm innovation performance, (2) examine the moderating role of executive academic backgrounds, (3) analyze the paths for firms to leverage knowledge spillovers from regional universities to promote firm innovation by their geographic location.A social network approach is used to construct alumni relationship networks of A-share listed companies in Shanghai and Shenzhen, China. A two-way fixed effects model is used to assess the impact of firms’ structural position in executive alumni networks on firms’ innovation performance. In addition, the research also delves into the interactions between knowledge spillovers from geographic locations and executives’ alumni networks, aiming to elucidate their combined effects on firms’ innovation performance.This paper explores the curvilinear relationship between executive alumni networks’ centrality and firm innovation within the Chinese context. It also finds that in the positive effect interval on the right side of the “U-shaped,” the industry with the highest number of occurrences is the high-tech industry. Moreover, it elucidates the moderating influence of executives’ academic experience on the alumni networks-innovation nexus, offering a nuanced understanding of these dynamics. Lastly, we provide novel insights into optimizing resource allocation to leverage geographic knowledge spillovers for innovation.The study may not fully represent the broader population of firms, particularly small and medium-sized enterprises (SMEs) or unlisted companies. Future research could expand the sample to include a more diverse range of firms to enhance the generalizability of the findings.Firstly, companies can give due consideration to the alumni resources of executives in their personnel decisions, but they should pay attention to the rational use of resources. Secondly, universities should actively work with companies to promote knowledge transfer and collaboration.The findings help clarify the influence mechanism of firms’ innovation performance, providing theoretical support and empirical evidence for firms to drive innovation at the executive alumni relationship network level.